BAHASA PERSUASIF SELEBGRAM KOTA MAKASSAR DALAM MENAWARKAN PRODUK - Ahmad Ahmad Jaya; Usman Usman; Hasriani Hasriani (Titik Dua: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
The Persuasive Language of Makassar City Celebrities in Offering Products. This study aims to: (1) Describe the form of persuasive language of the Makassar City program in offering products. (2) Describe the function of the Makassar City program in offering products. This type of research is qualitative research using descriptive methods. The focus of this research is phrases, clauses, and sentences. The source of the data in this study is celebgram. Data collection techniques are carried out by screen recordings, screenshots and observations. The research instruments consist of researchers, recording tools, and data analysis guides. The results of the study revealed that the persuasive forms used by the program when offering products, namely the form of affirming, the form of rewards, the form of offering several products, the form of praise, the form of swabbing, the form of persuasive language convincing, the form of persuasive language in the form of an invitation, the form of persuasive language in the form of orders, the form persuasive language in the form of asserting, persuasive language forms in the form of questions, forms of guarantees, forms of follow-up and forms of diverting attention. The function of persuasive language used by program celebrities is the function of providing information, the function of introducing products, the function of adding value. The use of several persuasive forms is due to consumers coming from different backgrounds. The use of various persuasive language functions so that consumers are more confident in choosing the products offered.